The Effect of Using Fluid Balance Application on Interdialytic Weight Gain in Stage V Chronic Kidney Disease Patients Undergoing Hemodialysis - Danny Putri Sulistyaningrum; Maya Cobalt Angio Septianingtyas; Tia Nurhanifah; Naylul Izza (Babali Nursing Research, 2023)
Chronic Kidney Disease (CKD) grade V is a condition that requires the patient to undergo hemodialysis for the rest of his life. Often hypervolemia occurs between two times of dialysis. Hypervolemia can lead to emergency conditions such as pulmonary edema and cardiac arrest. Interdialytic Weight Gain (IDWG) is an indicator of fluid intake during the interdialytic period. Calculating fluid balance per 24 hours helps patients with CKD grade V in controlling fluid intake. The purpose of this study was to identify the effect of using a fluid balance application on IDWG status in grade V CKD patients undergoing hemodialysis. This study used a quasi experiment, with one group pre and posttest design. 24 respondents were selected by consecutive sampling technique. Statistical analysis using a paired t-test showed that there was an effect of using a fluid balance application on IDWG status in grade V CKD patients undergoing hemodialysis (p value = 0.000). The application of fluid balance can be applied to patients with CKD grade V because it is effective in controlling hypervolemia